Clinical pharmacology in dental practice - Bautista, Magdalena B.; Banzuela, Alice T.;De Los Trinos, Ma. Isabel B.;Del Rosario, Alejandro;Valdoria, Rustico Za (Mandaluyong City, Philippines : National Book Store, 1976)
Beautiful Philippines in panoramic music, as the title suggests, seems like a dreamland vista of the Philippines in music. Indeed it is like it. This book has been prepared by the authors and compilers in response to the needs of Philippine schools, public and private.
Unit I : The Primary fundamentals of music -- Unit II : Warming-up and inspirational songs -- Unit III : Folk songs of our country and other lands -- Unit IV : Spanish time songs -- Unit V : Early American regime songs -- Unit VI : Songs of later American regime to Commonwealth period, 1916-1946 -- Unit VII : More fundamentals of music -- Unit VIII : Selections from foreign masters -- Unit IX : Songs for different occasions -- Unit X : Liberation period - Christmas carols -- Unit XI : Still more fundamentals of music -- Unit XII : Our contemporary music -- Unit XIII : Patriotic anthems and songs -- Unit XIV : Religious hymns -- Unit XV : Development of Philippine music and dances -- Unit XVI : Filipino musicians and composers -- Unit XVII : Foreign masters
Includes bibliographical references.
Keywords: PANORAMA MUSIC -- PHILIPPINES